Pengimplemetasian Wordwall sebagai Media Pembelajaran Bumbu Dasar pada Siswa SMK Kuliner - Graciella Yolanda; Yunus Karyanto; Julysa Ahmad Ardiansyah; Faedah Nur Baeti; Jihan Aulia Rahmah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This wordwall implementation research aims to describe the design of the interactive learning media development process using the Four-D (4D) model on basic spice material. This study uses a quantitative descriptive method to convey the application of the Four D model. The results of this media development received validation from media experts with a very good predicate and validation from material experts with a very good predicate. The results of this learning media development go through a series of stages as follows. 1) Define is the researcher conducting an analysis for information collection, non-cognitive diagnostic assessment analysis, concept analysis and specific objectives and reflection which will later be given to students in small groups, 2) Design is the researcher starting to choose media with the desired format. The chosen learning media is Wordwall, 3) Development is the beginning of the researcher in pouring ideas in the previous stage into the Wordwall learning media, 4) Dissemination is the dissemination stage, this Wordwall learning media is ready to be applied to vocational high school students majoring in culinary. The results of the application of this Four-D model get development results that can be used for learning media for culinary students.